Romantic Music: A History of Musical Style in Nineteenth-Century Europe - Plantinga, Leon (New York Norton, 1984)
Beginning with Beethoven's middle years, the author weaves a narrative in which major composers such as Schubert, Rossini, Liszt, Chopin, Berlioz, Schumann, Wagner, Verdi, Tchaikovsky, and Musorgsky are discussed in historical context. Professor Plantinga also places into clear focus slightly lesser figures such as Mendelssohn, Smetana, Dvorak, and others. In a final section that embraces Brahms, Mahler, Bruckner, Strauss, and Wolf, Plantinga rounds out this fascinating survey of the diverging movements and styles that constitute the Romantic century's legacy to the musical arts.
Keywords: 19th Century (1801-1900); Music history; Romanticism